2001
DOI: 10.1111/j.1349-7006.2001.tb01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of BRCA1 and BRCA2 mRNA Expression in Sporadic Breast Carcinomas and Its Relationship with Clinicopathological Characteristics

Abstract: BRCA1 and BRCA2 mRNA expression in sporadic breast cancers was quantified by a real-time reverse transcriptase-polymerase chain reaction (RT-PCR), and the relationship of their expression with various clinicopathological factors was studied. BRCA2 mRNA levels (0.993 ± ± ± ±1.395, mean ± ± ± ±SD (BRCA2/β β β β-glucuronidase mRNA ratios)) were significantly (P < < < <0.01) higher than BRCA1 mRNA levels (0.519 ± ± ± ±0.570 (BRCA1/ β β β β-glucuronidase mRNA ratios)), and a weak but significant (r = = = =0.390, P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Consistent with our previous report, 20 we have shown, in the present study, that upregulation of BRCA2 mRNA is associated with an aggressive phenotype of breast tumors, i.e., high histologic grade and ER negativity. In addition, we have previously shown that high BRCA2 mRNA levels are associated with high mitotic activity and nuclear pleomorphism.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with our previous report, 20 we have shown, in the present study, that upregulation of BRCA2 mRNA is associated with an aggressive phenotype of breast tumors, i.e., high histologic grade and ER negativity. In addition, we have previously shown that high BRCA2 mRNA levels are associated with high mitotic activity and nuclear pleomorphism.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we have previously shown that high BRCA2 mRNA levels are associated with high mitotic activity and nuclear pleomorphism. 20 These results are consistent with a model in which BRCA2 exerts a positive effect on proliferation. Such a model, however, is very unlikely to reconcile with the fact that BRCA2 is a tumor-suppressor gene that should inhibit proliferation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations